Analysis and design of a passive regenerative inductor-capacitor-diode snubber for DC link over-voltage mitigation in Y-source inverter - Diver, Rodrigo P. [UNESP]; Santos, Rafael [UNESP]; Gonçalves, Flávio A. S. [UNESP] (Wiley, 2024)
Renewable energy-based distributed generation presents new challenges for power inverters, requiring greater flexibility, reliability, cost-effectiveness, and efficiency. Impedance source network-based inverters (INIs) are an attractive option for addressing some of these issues since they provide a single-stage power conversion structure with buck-boost capability, allowing them to manage shoot-through conduction on the inverter arms. However, some INI topologies based on magnetic coupling, such as those of the Y-source impedance network family, have problems related to overvoltages at the power switches because of the presence of unwanted leakage inductances in the coupled-inductor windings. The insertion of the regenerative and passive LCD snubber in the impedance network circuit is a solution to mitigate this problem, but there is currently a lack of a clear and concise methodology to design its components, which hinders a wider adoption of this solution in different types of INI. This paper presents a comprehensive and analytical design for determining LCD snubber components. This study was carried out with the quasi-Y-source inverter, but the same methodology can be extended to other types of INI based on the Y-source network.
Keywords: DC-link overvoltage; impedance-source network; LCD snubber; quasi-Y-source inverter